Pencirian Sebatian Aktif Biologi daripada Alga Marin, Laurencia cartilaginea dan Hypnea pannosa - B. Ahmad, Fasihuddin (Universiti Putra Malaysia Press, 1994)
The chemical components and the biological activity of Laurencia cartilaginea and Hypnea pannosa have been studied. Extraction and purification of H. pannosa have resulted in the isolation of two monoterpenes identified as 3-bromo-8chloro- 6-- chloromethyl-2-methylocta-l ,6-diene (1) and 8-chloro-6--chloromethyl3- methoxy-2-methylocta-l,6-diene (2). The study of L. cartilaginea resulted in the isolation of a sesquiterpene identified as 8-bromochamigra-1,11 (12)-diene-9-0l (3). All the halogenated compounds showed some antibacterial properties.